PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS AUGMENTED REALITY DENGAN APLIKASI ASSEMBLR EDU UNTUK MENINGKATKAN PENALARAN MATEMATIS SISWA - Siti Khayroiyah; Dara Fitra Dwi; Irwansyah, Irwansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Development of Augmented Reality-Based Learning Media with the Assemblr EDU Application to Improve Students' Mathematical Reasoning. This research is motivated by the need to improve students' mathematical reasoning skills, which are important competencies in mathematics learning. Technology-based learning media such as Augmented Reality (AR) have great potential to make learning more interesting and interactive, so that it can improve students' understanding of mathematical concepts. Develop Augmented Reality-based learning media using the Assemblr EDU application. Assess the effectiveness of the learning media in improving students' mathematical reasoning. This study uses the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. Identify learning needs and analyze materials that are appropriate to be applied with AR. Design AR-based learning media using the Assemblr EDU application. Create learning media and AR content according to the specified design. Apply learning media to students in a classroom setting. Measure the effectiveness of learning media through mathematical reasoning tests and feedback from students. Media Development: AR-based learning media with the Assemblr EDU application has been successfully developed and tested. The level of technological readiness (TKT) for the use of AR-based learning media shows a significant increase in students' mathematical reasoning abilities. Students become more interested and motivated in learning mathematics. Student Feedback: Students gave positive responses to the use of AR media, stating that learning became more enjoyable and easier to understand. The development of Augmented Reality-based learning media using the Assemblr EDU application is effective in improving students' mathematical reasoning. AR technology makes learning more interactive and interesting, so it can be used as an innovative alternative in learning mathematics in schools.